2004
DOI: 10.1002/app.21104
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and physical properties of woolen fabrics cured with citric acid and chitosan

Abstract: ABSTRACT:In this study, we used citric acid (CA) as a crosslinking agent, mixed with biopolymer molecular chitosan, to perform a pad-dry-cure treatment on woolen fabrics to study its antimicrobial effects and physical properties with the help of IR spectroscopy, electron microscopy, and differential thermal analysis. From the experimental results, we learned that CA did not crosslink with the woolen fibers if the woolen fabrics were not oxidized by potassium permanganate and that after oxidization, CA produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(49 citation statements)
references
References 21 publications
(20 reference statements)
1
42
0
2
Order By: Relevance
“…Thus, it is concluded that under the conditions of these experiments, chitosan and citric acid reacted to form an acyclic amide. This is analogous to reports of woolÁcitric acid derivatives prepared by a similar technique (17).…”
Section: Resultssupporting
confidence: 89%
“…Thus, it is concluded that under the conditions of these experiments, chitosan and citric acid reacted to form an acyclic amide. This is analogous to reports of woolÁcitric acid derivatives prepared by a similar technique (17).…”
Section: Resultssupporting
confidence: 89%
“…It is made up of more than 18 amino acids, which can be alienated into four distinct groups: cationic, anionic, non-polar and polar. The main functional groups include carboxyl, amino and hydroxyl groups [33]. Overall, all wool fibers exhibited similar absorption at 3260 cm Fig.…”
Section: Fig 1 (A) Uv-visible Spectra (B) Ft-ir Spectra (C) Sem mentioning
confidence: 83%
“…4. In the FTIR spectroscopy, the main characteristic peaks appeared between 1,000 and 1,700 cm -1 , which are related to amide I (1,600-1,700 cm -1 ), amide II (1,500-1,600 cm -1 ), and sulfoxide (1,000-1,150 cm -1 ) [26]. Plasma treatment with oxygen gas can impart or enhance functional groups on the surface of textile substrate [27].…”
Section: Resultsmentioning
confidence: 99%